Patient perspectives of atopic dermatitis: comparative analysis of terminology in social media and scientific literature, identified by a systematic literature review. (24th August 2022) - Silverberg, J.I.; Feldman, S.R.; Smith Begolka, W.; Johnson, M.B.; Stanojev, C.; DiBonaventura, M.; Rojo Cella, R.; Valdez, H.; Feeney, C.; Thyssen, J.P.
Abstract: Atopic dermatitis (AD) is a chronic skin disease that significantly impacts patient quality of life (QoL). It is unknown whether patients and physicians have the same interpretation of AD burden. Unmet needs and AD disease burden were evaluated by comparing terminology used in social media with terminology used in scientific literature. AD terminology in social media was identified using the NetBase platform, and natural language processing was performed. Topics and words driving negative sentiment were evaluated overall and in relation to specific symptoms. The systematic review of scientific literature identified publications that included AD and QoL terms was identified from PubMed. Term analysis of titles and abstracts was conducted via natural language processing. The occurrence of topics and co‐occurrence of words associated with QoL terms were evaluated. More than 3 million social media mentions (2018–2020) and 1519 scientific publications (2000–2020) were evaluated. There were more negative than positive social media mentions, and flare and pain were common symptoms driving negative sentiment. Face and hands were major drivers of negative sentiment in relation to AD symptoms in social media. Sleep and pain were often mentioned together. In scientific literature, pruritus and depression were the most frequently occurring symptoms. Similarly, pruritus was the most common AD symptom co‐occurring with QoL terms in the assessed scientific literature. Social media analyses provide a unique view into the patient experience of AD. Symptoms driving negative sentiment in social media appear to be discordantly represented in scientific literature. Incorporating patient perspectives may improve disease understanding and management.